PENGEMBANGAN MEDIA PEMBELAJARAN MODUL ELEKTRONIK INTERAKTIF PADA MATA PELAJARAN EKONOMI UNTUK KELAS X LINTAS MINAT EKONOMI SMA LABORATORIUM UM KOTA MALANG - Lilik Sufiyah; Hadi Sumarsono (Jurnal Pendidikan Ekonomi (Economic Education Journal), 2015)
Good learning process and balanced course will emphasize the mutual interaction between teachers and students with teaching materials and media utilizing existing learning as a learning resource. Existing learning resources such as books or print modules but still minimal utilization technology. Therefore, innovation is needed in order to facilitate the learning process is the utilization of information and communication technologies, one of which is altering the packaging print modules into interactive electronic module. This research is a product development research in the form of interactive electronic media learning modules and tested for class X students across the economic interests SMA Laboratorium UM Malang. The model used in the development of instructional media is procedural model that refers to the Borg & Gall development model that has been modified according to the needs of researchers to outline the steps to be followed to produce the final product. The results of this study are: (1) media learning modules interactive electronic has been fit for use after passing the validation of expert materials and expert instructional media, (2) the results of testing the use of the subject of the trial is that there is a difference in value between before taught with instructional media module interactive electronic after learning modules taught with interactive electronic media.